(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the botanical origin, the temporal effect on the concentration of nutrients, the production potential, and the nutritional value of bee pollen produced in the city of Serra Talhada-PE. The fieldwork was carried out from April 2014 to March 2015. The collection of bee pollen was carried out fortnightly in four hives. Analysis of botanical origin and nutritional analyzes of pollen were performed regarding the percentage of crude protein and ether extract. Generalized linear models and Spearman correlation between variables were used. 63 pollen types were found, distributed in 21 families, 39 genera, 34 species and 11 indeterminate types. The families most represented in numbers of species were Leguminosae and Malvaceae. The production of bee pollen was higher in the rainy season than in the dry season, being negatively related to temperature and positively to humidity. The nutritional value of the collected pollen changed over the sampled months. There was no relationship between the levels of crude protein and ether extract with the number of pollen types and with precipitation. Based on the pollen analysis, it can be inferred that the studied Caatinga area maintains a great diversity of sources of resources for bees, with the Leguminosae family being responsible for the largest food supply for the same. This study shows that the vegetation located in Serra Talhada-PE presents plant species with high nutritional content and great potential for the production of bee pollen.